Biogas Production from Palm Oil Mill Effluent at Low pH - Zainal B.S.; Wan Mohd Farred W.A.F.; Mohamed H.; Mohamad Aziz N.A.; Junoh H.; Shamsuddin A.H. (Institute of Physics, 2024)
The palm oil industry in Malaysia has aided our economy, but with any thriving industry comes the baggage of industrial waste. This paper focuses on palm oil mill effluent (POME), a waste product formed by palm oil milling operations. The objective of this paper is to evaluate the ability of POME to generate biogas through acid and heat pre-treatment methods. The feasibility of producing biogas at pH levels lower than 5 was investigated. The inoculum is effective microbe 1 (EM1), and the substrate is a liquid POME. Hydrochloric and phosphoric acid were used in this study, and the effect of low initial pH on biogas generation was investigated. The results show that POME alone produced the highest biogas volume (20.1 Nml). However, POME incubated with activated EM1 inoculant at low pH (3.74) generated consistent biogas during 57.75 hours of digestion. In conclusion, the EM1 is a good source of inoculum for POME treatment at low pH, with no pre-treatment required. The pre-treatment methods proposed in this study could have opened new doors for bio-renewable energy research, particularly in agricultural biomass, since substrate pre-treatment can enhance biogas production. 2023 Institute of Physics Publishing. All rights reserved.